PENGEMBANGAN MATERI MENULIS TEKS BERITA BERBASIS KARYA WISATA UNTUK SISWA SMP - Bayu Andika; Edi Suyanto; Muhammad Fuad (Universitas Lampung, 2020)
Aim of this research is developing learning module for writing text-based news on tourism works and teach their feasibility in learning write news texts based on tourism work for junior high school students. This research uses development through the Borg and Gall model. The procedures in this research are (1) preliminary research, (2) module development material, and (3) product or module results. Data sources in the field trials were carried out in three schools, SMP Ngaras 1, SMP Negeri 2 Ngaras, and SMP Negeri 3 Bengkunat Belimbing. Data analysis techniques was carried out in a qualitative way. The results of this research can conclude